Functional hearing deficits in children with Type 1 diabetes. Issue 9 (12th February 2016) - Rance, G.; Chisari, D.; Edvall, N.; Cameron, F.
Abstract: Aim: Hearing loss (as reflected by abnormal sound detection) is a frequently reported consequence of Type 1 diabetes mellitus. We sought to evaluate sound detection, auditory neural function and binaural processing ability in a group of school‐aged participants with Type 1 diabetes and to assess their functional hearing and general communication ability. Methods: A range of electroacoustic, electrophysiological and behavioural test techniques were used to evaluate both cochlear and auditory neural function in 19 affected children. A cohort of matched controls was also assessed. Results: Although all of the participants with Type 1 diabetes enjoyed normal sound detection, 9 of the 19 (47%) showed evidence of auditory pathway abnormality with evoked potential latencies and/or amplitudes beyond age‐related norms. Auditory brainstem response interpeak latencies (wave I–V) were longer than in matched controls [ 95% confidence interval (95% CI); 0.10, 0.28 ms: P < 0.001] and wave V amplitudes were reduced (95% CI; –0.21, 0.00 μV: P = 0.02). Binaural speech perception in noise was also impaired (95% CI; 0.82, 3.17 dB: P = 0.002) and perceptual ability was correlated with degree of neural disruption in the auditory brainstem ( r = 0.662, P = 0.003). Conclusions: Hearing deficits severe enough to restrict communication and threaten academic progress were common on our group of school‐aged children with Type 1 diabetes. Evaluation of both cochlear and auditory neural function may form an important part of the standard management regime for children with diabetes. What's new?: This study explores functional hearing deficits in children with Type 1 diabetes. As such, it differs from most work in this field, which has only considered the effect of diabetes on sound detection ability. We demonstrate auditory pathway disorder in individuals with normal sound detection thresholds and consider the underlying mechanisms. The findings highlight binaural processing deficits and their effect on speech processing in background noise. Everyday listening ability is considered, as are potential developmental risks.